INTERNET TARMOG‘IDA SO‘Z ERKINLIGINI TA’MINLASHNING XALQARO-HUQUQIY VA YEVROPA STANDARTLARI - Nizamova Iroda Eldorjon qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2026)
The article examines the general principles of ensuring freedom of expression on the Internet in international and European law. It analyzes universal international legal guarantees of freedom of expression established in the Universal Declaration of Human Rights and the International Covenant on Civil and Political Rights, as well as European standards developed under the Charter of Fundamental Rights of the European Union and the European Convention on Human Rights. Particular attention is paid to permissible restrictions on freedom of expression, the criteria of legality, legitimate aim, necessity and proportionality, as well as the case-law of the European Court of Human Rights. The article argues that in the digital environment traditional standards of protection of freedom of expression remain relevant, but require more precise application, taking into account the speed of information dissemination, the cross-border nature of online communication, and the risks of disinformation and hate speech.